Perancangan Website Blogger UMKM “Sarapan Pagi Chaca Cake” Sebagai Media Pemasaran Produk - Rizelda Aswirdinata; Lidya Devega; M. Ilham Afriasnyah; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The influence of technology today can change the marketing strategies of all business people. Where the right business strategy in this advanced era will advance the business. This encourages businesses to adopt innovative marketing strategies, especially through online media. This article documents the design and implementation of an eCommerce website for MSMEs offering breakfast, with a focus on the case study “Breakfast Chaca Cake”. In this project, we chose the Blogger platform as the main development tool to create the website. Some of the stages of website creation carried out are data collection, system analysis, website design using the blogger platform. This project aims to increase product exposure, expand market reach, and improve the marketing and product promotion process for MSMEs. The result of the implementation of this project is a website https://chacacake1103.blogspot.com/. This project is expected to be useful for Chaca Cake Breakfast MSMEs which can increase the number of customers.